Pendidikan Kesehatan tentang Kepatuhan Minum Obat terhadap Tingkat Pengetahuan Keluarga Pasien Skizofrenia di Wilayah Kerja Puskesmas Gerung Kabupaten Lombok Barat - Ni Nyoman Santi Tri Ulandari; Sri Masdiningsih Utami; Ni Luh Putu Wulandari (LPPM STIKES Mataram, 2023)
Introduction: Schizophrenia is one of the neurological mental disorders that affects the perception, way of thinking, language, emotions and social behavior of people who experience it. Families of patients who experience schizophrenia stop treatment because they feel that treatment is not needed and argues that schizophrenia cannot be cured, as well as the side effects of the drugs taken, such as a lot of sleep so that the family feels worried about the patient. Objective: To find out the effect of health education about drug compliance with drugs on the level of knowledge of the family of Schizophrenia patients in the working area of the Puskesmas Gerung West Lombok. Method: This research is a quantitative research with the pre -experimental design approach. Samples as many as 50 respondents, obtained with total sampling. The questionnaire is used to measure the level of knowledge and use the paired t-test test to see the effect of health education on the level of family knowledge. Results: The results show that before being given health education there were 28 respondents (56.0%) with less knowledge. After being given health education there were 28 respondents (56.0%) with good knowledge. P value is 0.000 <0.05 (α). Conclusion: There is an influence of health education about drug compliance with the level of knowledge of the family of Schizophrenia patients in the working area of the Gerung Health Center in West Lombok Regency.